2013
DOI: 10.4085/1062-6050-48.4.04
|View full text |Cite
|
Sign up to set email alerts
|

The National Sports Safety in Secondary Schools Benchmark (N4SB) Study: Defining Athletic Training Practice Characteristics

Abstract: Context: Increased rates of sport participation and sportrelated injury have led to greater emphasis on and attention to medical care of student-athletes in the secondary school setting. Access to athletic training services is seen as a critical factor for delivering adequate injury prevention and medical care to student-athletes. However, few data are available regarding practice characteristics of athletic trainers (ATs) in this setting.Objective: To characterize the practices of secondary school athletic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…A total of 79.4% of respondents indicated that their school had fewer than 399 female athletes, and 18.6% had more than 400 female athletes. 22 The secondary schools in the AT-PBRN are similar to those in the N4SB sample with respect to the public and private or parochial status and school enrollment but tended to have smaller numbers of both male and female athletes.…”
Section: Secondary School Cps Characteristicsmentioning
confidence: 81%
See 2 more Smart Citations
“…A total of 79.4% of respondents indicated that their school had fewer than 399 female athletes, and 18.6% had more than 400 female athletes. 22 The secondary schools in the AT-PBRN are similar to those in the N4SB sample with respect to the public and private or parochial status and school enrollment but tended to have smaller numbers of both male and female athletes.…”
Section: Secondary School Cps Characteristicsmentioning
confidence: 81%
“…Their average age was lower than the mean age of the N4SB respondents (27.3 6 7.0 years versus 35.7 6 9.9 years, respectively), and only 21.7% held a master's degree, compared with 55% of the N4SB sample. 22 Most secondary school clinicians practicing in the AT-PBRN had less than 5 years of clinical experience (78.2%); only 30.7% of the N4SB sample reported practicing for less than 5 years. These findings are not surprising considering that the AT-PBRN partnered with postprofessional athletic training education programs to enroll secondary schools associated with these educational programs during the initial development of the AT-PBRN.…”
Section: Secondary School Clinician Characteristicsmentioning
confidence: 94%
See 1 more Smart Citation
“…With permission, we incorporated questions from the National Sports Safety in Secondary Schools Benchmark study. 19 Additionally, we compiled a combination of questions based on information from content experts. The survey, titled ''The Beliefs, Attitudes and Knowledge Following Pediatric Athlete Concussions among athletic trainers employed in the secondary school setting'' (BAKPAC-AT), consists of 3 sections: (1) concussion management and care, (2) concussion referral, and (3) AA.…”
Section: Instrumentationmentioning
confidence: 99%
“…The medical professional best suited to provide medical care to high school athletes is a certified athletic trainer (AT). 1 The AT is the ideal liaison among school administrators, coaches, physicians, and parents. 2 Although ATs are estimated to be present in 86% of all US high schools, only 36% of high school athletes have access to a full-time AT.…”
mentioning
confidence: 99%